High resolution aerosol jet printing of conductive ink for stretchable electronics - Goh, Guo Liang (2018)
Stretchable electronics is gaining wide spread attention due to its application in many applications such as wearable devices, soft robotics, biomedical and consumer products. Aerosol jet printing, which is capable of printing very fine features, can be used to fabricate high performance flexible electronic devices. In this paper, we explore aerosol jet process technique to print conductive stretchable ink for fabricating new-age electronic circuits. Functional composite ink made of silicone and silver composite were used to print directly on stretchable silicone rubber substrate. Electronic functional devices such as flexible circuit and strain gauge were successfully printed, characterized and tested for stretchability.